Funding Innovation in Poland through Crowdfunding - Katarzyna Kozioł-Nadolna (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Funding innovative projects is one of the most serious problems faced by business owners in Poland. Therefore, due to the difficulties of obtaining external sources of financing, crowdfunding may constitute a new source of fundraising for innovative ventures. Therefore, crowdfunding – as a way of raising capital for projects – is the subject of the discussion in this article. The research aim of the article is to identify and evaluate crowdfunding platforms as well as the innovative projects carried out by these platforms in Poland in 2014-2016. The first part characterizes crowdfunding as a source of funding innovation and presents the nature of crowdfunding, its characteristics and models. The empirical part is based on inductive-deductive inference, desk research, i.e. the analysis of crowdfunding market in Poland in two research periods and a case study analysis. The article shows the results of the research on the Polish crowdfunding market in 2014-2016. The author also presents a case study of funding innovation on the Kickstarter.com platform by a Polish company Sher.ly.